2005
DOI: 10.1111/j.1365-2141.2005.05722.x
|View full text |Cite
|
Sign up to set email alerts
|

State and diagnostic value of plasma tissue factor in early‐hospitalised patients with chest pain

Abstract: SummaryTo study the state and diagnostic value of plasma tissue factor (TF) in patients with acute coronary syndromes (ACS), we quantitatively compared plasma TF antigen and TF activity in 90 early-hospitalised patients with chest pain. Using high-affinity antibodies, a sensitive assay for TF antigen was developed with a detection limit of 40 fmol/l. One of the antibodies was used to capture TF from plasma and, after elution and dialysis-free reconstitution in phospholipid-glucoside micelles, absolute amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Circulating TF is a balance between excretion and immobilization of the molecule from activated monocytes, endothelial cells or subendothelial lineage from an inflamed site on a vessel. Although there is still an ongoing debate about the functional role of TF in the circulation [21,22], it has recently been shown that circulating TF is (potentially) active but inhibited in vivo [19]. In addition, our results suggest that high production on inflamed sites does not warrant high circulating levels.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Circulating TF is a balance between excretion and immobilization of the molecule from activated monocytes, endothelial cells or subendothelial lineage from an inflamed site on a vessel. Although there is still an ongoing debate about the functional role of TF in the circulation [21,22], it has recently been shown that circulating TF is (potentially) active but inhibited in vivo [19]. In addition, our results suggest that high production on inflamed sites does not warrant high circulating levels.…”
Section: Discussionmentioning
confidence: 61%
“…Thirdly, in our study we measured TF antigen levels, whereas other studies have measured TF activity. In patients with acute coronary syndromes, antigen levels are 20-30% higher than activity levels, and correlation coefficients of approximately 0.5 between activity and antigen have been described [19]. Finally, TF activity is influenced by natural positive and negative feedback mechanisms, i.e.…”
Section: ó 2006 International Society On Thrombosis and Haemostasismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ]. The increase in TF activity observed in the present study, might reflect a systemic hypercoagulable state [ 29 , 30 ]. There is growing evidence that circulating TF is potentially active in an encrypted state, where it can bind FVII, but lacks proteolytic activity [ 31 ].…”
Section: Discussionmentioning
confidence: 82%
“…As aconsequence of elevatedprocoagulant activity,higher levels of coagulation markers such as prothrombin fragment 1.2 (F1.2), thrombin-antithrombin complex (TAT ), fibrinopeptide A, the D-dimer,soluble fibrinogen, etc.are observed (7)(8)(9)(10). Although therea re studiess uggesting elevatedc oncentrations of soluble TF in plasma of CAD patients, the prognosticvalue of TF assays remains controversial (11)(12)(13). Forexample, Campo et al suggested that plasma TF levelisapredictor of mortality in patients with acute MI (13),while other authorsreport no significant differences in TF activity (12)orantigen (11) betweenACS patients and stable controls.…”
Section: Introductionmentioning
confidence: 99%